2021
DOI: 10.1017/s1092852920002370
|View full text |Cite
|
Sign up to set email alerts
|

Lumateperone (ITI−007) in the Treatment of Bipolar Depression: Results from a Randomized Clinical Trial

Abstract: Study ObjectiveApproved treatments for bipolar depression are limited and associated with a spectrum of undesirable side effects. Lumateperone (lumateperone tosylate, ITI−007), a mechanistically novel antipsychotic that simultaneously modulates serotonin, dopamine, and glutamate neurotransmission, is FDA-approved for the treatment of schizophrenia. Lumateperone is currently being investigated for the treatment of bipolar depression (major depressive episodes [MDE] associated with bipolar I and bipolar II disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…19 Lumateperone is unique in that it modulates serotonin, dopamine and glutamate simultaneously. 5 In a study of 377 patients, lumateperone had significantly greater MADRS response rate (51.1% vs 36.7%; OR=2.98, p<0.001) and remission rate (p=0.02) at day 43 compared with placebo. 5 Participants in this study reported good tolerability of lumateperone with relatively low risk of EPS, metabolic changes and prolactin elevation.…”
Section: Cariprazine (Approved In 2019)mentioning
confidence: 95%
See 3 more Smart Citations
“…19 Lumateperone is unique in that it modulates serotonin, dopamine and glutamate simultaneously. 5 In a study of 377 patients, lumateperone had significantly greater MADRS response rate (51.1% vs 36.7%; OR=2.98, p<0.001) and remission rate (p=0.02) at day 43 compared with placebo. 5 Participants in this study reported good tolerability of lumateperone with relatively low risk of EPS, metabolic changes and prolactin elevation.…”
Section: Cariprazine (Approved In 2019)mentioning
confidence: 95%
“…In a study of 377 patients, lumateperone had significantly greater MADRS response rate (51.1% vs 36.7%; OR=2.98, p<0.001) and remission rate (p=0.02) at day 43 compared with placebo 5. Participants in this study reported good tolerability of lumateperone with relatively low risk of EPS, metabolic changes and prolactin elevation 5. In the most recent clinical trial, mean changes from baseline in weight, fasting glucose, total cholesterol, triglycerides and low-density cholesterol were similar between lumateperone and placebo 19.…”
Section: Fda-approved Medications For Treatment Of Bd-dmentioning
confidence: 95%
See 2 more Smart Citations
“…In pre-approval clinical trials, it demonstrated efficacy in lowering psychotic symptoms during acute schizophrenia and a good short-term safety/tolerability profile with only somnolence/sedation indexes significantly higher than placebo [ 50 ]. Lumateperone’s pharmacodynamic profile suggested its hypothetical efficacy in bipolar depression and the results coming from the first trials tend to confirm the hypothesis [ 51 53 ]. No clinical trials of lumateperone in bipolar mania have been performed to our knowledge.…”
Section: Emerging Approaches To the Treatment Of Maniamentioning
confidence: 99%